Tourism Site Recommender System Using Item-Based Collaborative Filtering Approach - Robertus Adi Nugroho; Agnes Maria Polina; Yohanes Dicky Mahendra (Universitas Sanata Dharma, 2020)
Many people like traveling. But, often they are difficult to find a tourism site that they like much. Too many information about tourism is the problem. To overcome this problem, we need to filter the information. Recommender System could filter the information. By considering the advantages, the system used item-based collaborative filtering approach to give recommendation. Some tourism site around Yogyakarta province were used in this research. The system is able to give recommendation to users. The accuracy of the rating prediction is 0,6293 and the average time consumption is 1693,33 millisecond.